2017
DOI: 10.1002/jcp.26117
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondrial ROS in antibacterial immunity

Abstract: Reactive oxygen species (ROS) are essential participants of various innate immune cell responses against microorganisms and are also involved in many cellular regulatory pathways. It was believed that the main pool of ROS in the innate immune cells is generated by the NADPH oxidase enzymatic complex. However, it was discovered recently that mitochondrial ROS (mtROS) are equally important for the functioning of the immune system. mtROS play an important role in the development of the antimicrobial innate immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 94 publications
(137 reference statements)
1
42
0
Order By: Relevance
“…mtROS have also been increasingly reported to contribute to both innate and adaptive immunity [34, 50], and increased production of mitochondria-derived species likely explains the Pam2-ODN-increased superoxide we detect [23].…”
Section: Discussionmentioning
confidence: 99%
“…mtROS have also been increasingly reported to contribute to both innate and adaptive immunity [34, 50], and increased production of mitochondria-derived species likely explains the Pam2-ODN-increased superoxide we detect [23].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria can also act as an ROS‐producing organelle . This mechanism has been shown to play a role in host defense from pathogens by macrophages .…”
Section: Functional Diversity In Phagocytic Cellsmentioning
confidence: 99%
“…For a long time, it was believed that mitochondria do not play a significant role in the functioning of neutrophils, since their content in these cells is low, energy supply is supported by glycolysis, and NADPH oxidase is the main source of ROS. Subsequently, however, it turned out that mitochondria are involved in the transmission of signals that determine main responses of the neutrophils to pathogens [ 14 ]. It was found that mitochondrial ROS are involved in the activation of NADPH oxidase and in the induction of NETosis caused by various stimuli [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%